Mafhum an-Nahyi Baina al-Balaghiyyin wa al-Ushuliyyin - Bambang, Bambang; Anas, Hazuar (ARABIYATUNA : Jurnal Bahasa Arab, 2017)
The Nahi study is one of the studies of concern among scholars Balaghah and Ushul fiqih. The source of the difference between the two branches of the discipline refers to the object of study and the goal to be achieved between the two. The object of Balajiah scholars study is related to the meaning of language contained in the uslub nahi and how the use of uslub nahi in the language of good communication and effective so that there is no communication error between the speaker and the other person. The result of their discussion is that the uslub nahi contains two meanings namely the essential meaning and metaphor. The intrinsic meaning is the prohibition arises from a speaker whose position is superior to the opposite speaker, while the meaning of metaphoric is contrary to the intrinsic meaning, and this change of meaning can be analyzed through the context of the use of language. As for ulama ushul fiqih, their study of nahi is not to explore the meaning of the language contained in uslub nahi, but focused to explore the content of islamic law contained in uslub nahi. The conclusion of their study that nahi sometimes implicate the law cancellation of something that is prohibited either in the form of acts or the other, and sometimes also nahi not implicate cancellation of what is prohibited.